PENGARUH KEMAMPUAN MANAJERIAL DAN LINGKUNGAN SERTA MOTIVASI TERHADAP KINERJA GURU SMA NEGERI DIMUSI BANYUASIN - Englasari, Englasari (Universitas muhammadiyah palembang, 2017)
This study aims to determine and analyze the effect og managerialability, environment, and motivation on the performance of high schoolteachers in State Musi Banyuasin senior high school. In this research usedassociative design. The variables used are managerial capability,environment, and motivation to techers performance with as a wholedeveloped into 28 indicators. Sampleswere taken as many as 118 techers bycluster sampling. The main data needed is primary data with questionnairedata collection method. Futher data analyzed using multiple linier regression.The result of the study found that there were significan influencessimultaneously with managerial, environmental, and motivational ability ofteacher performance. While the partial working environment does not give areal effect on teacher performance